Pediatric Pleomorphic Adenoma of the Palate - Jerome A. Lindeboom; Jean-Pierre T. F. Ho; Naomi Donner; Willem H. Schreuder (Case Reports in Dentistry)
Pleomorphic adenoma is the most common salivary gland tumor but is extremely rare in pediatric patients. The parotid gland is the most affected salivary gland, and the minor salivary glands are rarely affected. Here, we report a case of a 12-year-old boy with a pleomorphic adenoma of the palate.